2020
DOI: 10.1101/2020.07.13.200543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beat gestures influence which speech sounds you hear

Abstract: Beat gestures – spontaneously produced biphasic movements of the hand – are among the most frequently encountered co-speech gestures in human communication. They are closely temporally aligned to the prosodic characteristics of the speech signal, typically occurring on lexically stressed syllables. Despite their prevalence across speakers of the world’s languages, how beat gestures impact spoken word recognition is unclear. Can these simple ‘flicks of the hand’ influence speech perception? Across six experimen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Thus it is possible that differences in the phonetic realization of prominence may have had an effect. Conversely, other studies have also shown that when prosody is held constant, the presence of a beat gesture boosts the perception of speech prominence (Krahmer and Swerts, 2007;Bosker and Peeters, 2020). Even though our materials were controlled for the presence of pitch accentuation in beat positions across conditions, the fact that speech production was not kept completely constant does not rule out the possibility that pitch range differences might have had an effect on the results.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus it is possible that differences in the phonetic realization of prominence may have had an effect. Conversely, other studies have also shown that when prosody is held constant, the presence of a beat gesture boosts the perception of speech prominence (Krahmer and Swerts, 2007;Bosker and Peeters, 2020). Even though our materials were controlled for the presence of pitch accentuation in beat positions across conditions, the fact that speech production was not kept completely constant does not rule out the possibility that pitch range differences might have had an effect on the results.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, non-referential beat gestures are one of the most common types of gesture that are produced by speakers, particularly the case in academic contexts where these gestures predominate at rates of up to 94.6% of the gesture types produced (Shattuck-Hufnagel and Ren, 2018, see also Rohrer et al, 2019 for similar results). These gestures (much like their referential counterparts) are also integrated with speech prosody (often co-occurring with pitch accentuation), and their presence can actually modulate a listener's perception of prominence (see Krahmer and Swerts, 2007;Bosker and Peeters, 2020). Further, non-referential beat gestures have important discursive and pragmatic functions, such as marking information structure (Im and Baumann, 2020), epistemic stance (Prieto et al, 2018;Shattuck-Hufnagel and Prieto, 2019), among others.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that IW's gestures might not lose their efficacy when more variably timed; i.e., a statistical change then is not communicatively meaningful. On the other hand, gesture-speech timing incoherencies are in line with IW's phenomenology of a perceived sense of effort to gesture under the blind [5] , and it has been found that humans are able to be perceptually sensitive to syllable-level timing differences in gesture [44], [45]; in this sense the current timing variability is likely a meaningful difference.…”
Section: Discussionmentioning
confidence: 76%
“…While difference in timing variability between the blind and non-blind conditions is statistically clear, whether these differences impact communication is an empirical issue [44], [45]. It is possible that IW's gestures might not lose their efficacy when more variably timed; i.e., a statistical change then is not communicatively meaningful.…”
Section: Discussionmentioning
confidence: 99%
“…At the micro-level, a paper by Bosker & Peeters re-examines the ‘McGurk effect’ – where an auditory stimulus ‘ba’ is accompanied by a visual stimulus of the speaker's mouth movements that articulate a different sound ‘ga’ resulting in participants consistently reporting hearing ‘da’. 5 In the McGurk experiment, the visual stimulus strongly biases the auditory percept. In Bosker & Peeters’ study, instead of using video of the speaker's mouth movement, they examine how ‘beat gestures’ influence speech perception.…”
mentioning
confidence: 99%